Pneumoperitoneum by appendicular perforation - Sierra Obiol, Atanasio J (Cirugía del Uruguay, 2020)
A new case of pneumoperitoneum, diagnosed roentgenologically, and provoked by appendix perforation, is reported upon. Operative findings accounting for this uncommon -although not exceptionalclinico- radiological occurrence, are discussed.